Product Placement On Social Media The Influence Of Product Placement Towards Malaysian Consumer' Purchase Intention And Brand Perception - Teng, Jane Hui Ching (Universiti Malaysia Sarawak, (UNIMAS), 2017)
With the emerging of social media, product placement on social media was introduced which known as a new alternative marketing strategy. It was used to promote and sell the product or brand in the way of unobvious and strategically. However, the information was limited because it was a new scope of the study recently. It was unclear that the customers' real reaction towards product placement on social media in Malaysia. Therefore, this paper aimed to investigate the effectiveness of product placement on social media towards Malaysia customers' purchase intention and brand perception. The online questionnaire was prepared in order to be distributed to 400 Malaysia social media users and data was analyzed with SPSS. Subsequently, the scatter plot, correlation and regression analysis were used to determine the relationship between the variables. Based on the result of questionnaire survey, Malaysia social media users have positive attitude towards the celebrities or cewebrities that involved in the product placement on social media. The analyses showed that product placement on social media had strong positive impact on consumers' brand perception and purchase intention. In conclusion, product placement on social media was suitable to be applied in Malaysia.